India Summary of the Plans Central and Provincial Govt. - Government of India, Advisory Planning Board (Government of India, Advisory Planning Board, 1968)
The document summarizes the planning initiatives of India’s Central and Provincial Governments, highlighting their coordinated approach to post-independence socio-economic development. Plans are classified into provincial initiatives, central government projects, and major industrial development, with substantial financial allocations for irrigation, power, railways, education, and health. Industrial panels provided detailed recommendations for sectors such as textiles, plastics, glass, ceramics, sugar, leather, and vanaspati, emphasizing production expansion, research, and government support. The National Planning Committee framework underscores industrialization, self-sufficiency, equitable distribution, employment generation, and improving living standards. Overall, the plans advocate structured governance, resource mobilization, and state coordination to achieve balanced and sustainable economic growth across India.
Government of India, Advisory Planning Board
Keywords: Central Government Plans; Provincial Plans; Industrial Development; Economic Planning; Infrastructure; Agriculture; Education; Employment; Self-Sufficiency; Resource Mobilization